Cultured subventricular zone progenitor cells transduced with neurogenin-2 become mature glutamatergic neurons and integrate into the dentate gyrus. - Xia Chen (Public Library of Science (PLoS), 2012)
We have previously shown that transplantation of immature DCX+/NeuN+/Prox1+ neurons (found in the neonatal DG), but not undifferentiated neuronal progenitor cells (NPCs) from ventral subventricular zone (SVZ), results in neuronal maturation in vivo within the dentate niche. Here we investigated whether we could enhance the integration of SVZ NPCs by forced expression of the proneural gene Neurogenin 2 (NEUROG2). NPCs cultured from neonatal GFP-transgenic rat SVZ for 7 days in a non-differentiating medium were transduced with a retrovirus encoding NEUROG2 and DsRed or the DsRed reporter gene alone (control). By 3 days post-transduction, the NEUROG2-transduced cells maintained in culture contained mostly immature neurons (91% DCX+; 76% NeuN+), whereas the control virus-transduced cells remained largely undifferentiated (30% DCX+; <1% NeuN+). At 6 weeks following transplantation into the DG of adult male rats, there were no neurons among the transplanted cells treated with the control virus but the majority of the NEUROG2-transduced DsRed+ SVZ cells became mature neurons (92% NeuN+; DCX-negative). Although the NEUROG2-transduced SVZ cells did not express the dentate granule neuron marker Prox1, most of the NEUROG2-transduced SVZ cells (78%) expressed the glutamatergic marker Tbr1, suggesting the acquisition of a glutamatergic phenotype. Moreover, some neurons extended dendrites into the molecular layer, grew axons containing Ankyrin G+ axonal initial segments, and projected into the CA3 region, thus resembling mature DG granule neurons. A proportion of NEUROG2 transduced cells also expressed c-Fos and P-CREB, two markers of neuronal activation. We conclude that NEUROG2-transduction is sufficient to promote neuronal maturation and integration of transplanted NPCs from SVZ into the DG.